PEMBERDAYAAN MASYARAKAT SEBAGAI PROGRAM CSR PT NHM DI DESA BAILENGIT KECAMATAN KAO BARAT KABUPATEN HALMAHERA UTARA (STUDI ANTROPOLOGI PEMBANGUNAN) - Goleo, Arnol; Matheosz, Jenny Nelly; Mawara, Jetty E. T. (Universitas Sam Ratulangi, 2019)
The presence of corporate social responsibility Program (CSR) is a company's social response to the environment in various forms of activities. In addition, its activities are not only oriented to physical development, but there are also in non-physical forms for certain territories. One of the focuses of the non-physical activities of CSR is community empowerment. The goal is to have human resources in the company circles can be independent and skilled.CSR Program PT. Nusa Halmahera Mineral commenced since the enactment of limited liability company number 40 year 2007, where in article 74 paragraph 1 mentions that a limited liability company that conducts business in the field and or is concerned with Natural resources are obliged to carry out social and environmental responsibilities. Because the purpose of the company in running the business world is not merely pursuing profits or profits only. However, it embodies the welfare of the mining circle community, especially those in the West Kao. Therefore, the CSR program of PT. Nusa Halmahera Mineral is a manifestation of corporate concern to the surrounding environment, while also contributing to the economic development of the Community continually.Community Empowerment undertaken By PT. Nusa Halmahera Mineral through CSR Program is an obligation that must be done by the company for the benefit of the community, but in reality until now The CSR program has not run as it should. Many of the CSR programs do not precisely target the eventual lack of benefits gained by the community. Keywords: human resources, responsibility, company